Observations on the biology of Afrotropical Hesperiidae (Lepidoptera) with particular reference to Kenya. Part 10. Pyrginae, Carcharodini - Cock, Matthew J. W. (Zootaxa, 2016)
Partial life histories are presented for Spialia kituina (Karsch), S. spio (Linnaeus), S. diomus (Hopffer), S. colotes transvaaliae (Trimen), S. dromus (Plötz), S. ploetzi (Aurivillius), S. zebra bifida Higgins and Gomalia elma elma (Trimen). All feed on species of Malvaceae. An earlier record from Kenya of Melhania velutina as the food plant of S. depauperata depauperata (Strand) was based on a misidentification and there are no known records of the food plant of this subspecies. Spialia ferax (Wallengren) stat. rev. is considered a valid species rather than a subspecies of S. diomus, based on significant differences in wing patterns, the shape of the valves, a zone where neither occurs, no signs that a cline is involved, and differences in the colouring and markings of the caterpillars. The convergence of the biology of the chequered skippers of the tribes Carcharodini, Pyrgini and Celaenorrhini is discussed.